Estimation of solar energy potential in East Malaysia by using Satellite Images - Ayu Wazira, Azhari; Kamaruzzaman, Sopian; Abdul Haqi, Ibrahim (Universiti Malaysia Sarawak, 2010)
Faculty of Engineering, Universiti Malaysia Sarawak in collaboration with the Institution of Engineers, Malaysia (Sarawak Branch), 27th - 28th December at Kuching, Sarawak, Malaysia